Determination of cationic mobilities and pKa values of 22 amino acids by capillary zone electrophoresis - Vceláková, Katerina; Zusková, Iva; Kenndler, Ernst; Gas, Bohuslav (Electrophoresis, 2004)
The effective mobilities of the cationic forms of common amino acids--mostly proteinogenic--were determined by capillary zone electrophoresis in acidic background electrolytes at pH between 2.0 and 3.2. The underivatized amino acids were detected by the double contactless conductivity detector. Experimentally measured effective mobilities were fitted with the suitable regression functions in dependence on pH of the background electrolyte. The parameters of the given regression function corresponded to the values of the actual mobilities and the mixed dissociation constants (combining activities and concentrations) of the compound related to the actual ionic strength. McInnes approximation and Onsager theory were used to obtain thermodynamic dissociation constants (pK(a)) and limiting (absolute) ionic mobilities.
Keywords: Cations; Computer Simulation; Amino Acids; Kinetics; teoretické modely; kationty; Electrophoresis, Capillary; aminokyseliny; Models, Theoretical; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; kinetika; počítačová simulace; elektroforéza kapilární